Social Determinants of Health and Depression: A Preliminary Investigation from Rural China - Liang, Yuan; Gong, Yan-Hong; Wen, Xiao-Piao; Guan, Chao-Ping; Li, Ming-Chuan; Yin, Ping; Wang, Zhi-Qing (PLOS ONE, 2012)
Background In the last several years, research related to social determinants of health (SDH) has begun to resonate in the medical, behavioral, social and political sciences arena. The aim of the present study was to explore the relationship between SDH and depression, and to provide new evidences and clues for depression control and prevention. Methodology/Principal Findings This research was a cross-sectional survey executed door to door from October 2006 to April 2008, with a sample of 3,738 individuals aged 18 and older in rural China. The three variables of SDH were socioeconomic status (years of schooling and self-reported economic status of family), social cohesion and negative life events. Demographic variables and self-perceived physical health were taken as potential confounders. The cross-table analysis showed that variations in levels of depression were associated with variations in SDH, and logistic regression analysis confirmed the association even after adjusting for potential confounding variables. Conclusions Although there were some limitations, the current study provides initial evidence of the importance of SDH in depression. Findings indicate that social inequity and the role of policy action emphasized by SDH should be considered high priorities when addressing the issue of depression. In addition, cell-to-society and pill-to-policy approaches should be encouraged in the future.